2020
DOI: 10.1186/s12891-020-03261-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in chronic musculoskeletal symptomatic Chilean population: secondary analysis of National Health Survey 2009–2010

Abstract: Background: Health-related quality of life (HRQoL) is defined as the patient's perception of their health status. HRQoL can be modified by illnesses, treatments or social and health policies. Chronic musculoskeletal pain is a modifying factor of HRQoL that leads to lower quality of life, elevated suffering and disability. Knowing HRQoL in subjects reporting chronic musculoskeletal symptoms (cMSS), like pain, discomfort or swollenness lasting more than 3 months, will provide information to health teams and orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…MSDs have been an important factor associated with teachers' mental and physical health. Thus, our objective was to determine the association of MSD with QoL considering sociodemographic and body composition factors in urban and rural Chilean teachers; 89% of teachers presented pain in some part of the body, close to the highest pain prevalence of 95% found in teachers worldwide according to Erick and Smith (35) and is slightly higher than that reported by Solis-Soto in urban and rural Bolivian teachers at 86%, as well as being drastically higher than the prevalence in the general Chilean working population at 49.8% and the nationwide rate reported in the Chilean National Health Survey [(42.6%, (36)]. QoL evaluation in this study showed that differences exist between teachers with higher and lower PCS scores according to their number of painful MSD areas, a factor associated with the QoL PCS reported in previous studies (11).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…MSDs have been an important factor associated with teachers' mental and physical health. Thus, our objective was to determine the association of MSD with QoL considering sociodemographic and body composition factors in urban and rural Chilean teachers; 89% of teachers presented pain in some part of the body, close to the highest pain prevalence of 95% found in teachers worldwide according to Erick and Smith (35) and is slightly higher than that reported by Solis-Soto in urban and rural Bolivian teachers at 86%, as well as being drastically higher than the prevalence in the general Chilean working population at 49.8% and the nationwide rate reported in the Chilean National Health Survey [(42.6%, (36)]. QoL evaluation in this study showed that differences exist between teachers with higher and lower PCS scores according to their number of painful MSD areas, a factor associated with the QoL PCS reported in previous studies (11).…”
Section: Discussionmentioning
confidence: 57%
“…Prior studies suggest that female gender is an MSD risk factor (36,37). In this sense, female gender could be contribute to reporting MCS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, there are reports that 42.6% of the general working population has chronic work-related MSD, with symptoms presenting as risk factors strongly associated with low QoL scores, especially on the physical and mental health components ( 33 ). Therefore, the organizational context of teaching work in Chile and the world presents various physical and psychosocial deficiencies resulting in the presence of MSD and a concomitant deterioration in the mental and physical health of people.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies on the working population in the USA report high muscle pain prevalence related to low QoL scores ( 34 ); and studies on dockworkers in Brazil showed similar significantly lower scores on at least 5 of the 8 QoL scales on the SF-36 instrument among individuals with MSD ( 32 ). In the Chilean general population, people with chronic musculoskeletal pain have reported physical and mental QoL impacts, especially among women ( 33 ). Studies on the working population of Chilean teachers report high MSD prevalence in urban and rural teachers with significant QoL impact ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation